Model Pengembangan Bahan Ajar Bahasa Indonesia sebagai Mata Kuliah Wajib Umum (MKWU) Berbasis Paradigma Pembelajaran Abad Ke-21 pada Aspek Career and Life Skills (CLS) - Ajeng Tina Mulyana (Jurnal Inovasi Pendidikan MH Thamrin, 2018)
Preparing students to be skilled in work in the 21st century and able to connect a skill in 21st century teaching/Partnership for Teaching 21st Century Skill (P21) this articulates that students are expected to become successful individual citizens in working in the 21st. The pedagogic goes from traditional core skill to teaching paradigms of the 21st century. This 21st century paradigm is indispensable to ensure that at graduation students must be able to prepare themselves for work and other skills most in demand in the 21st century, namely career and life skills (CLS). This study aims to produce appropriate Indonesian language teaching materials with student learning needs in the 21st century. The research method used is development research (R D). This research will find and develop language teaching materials consisting of aspects of skills; listening, speaking, reading and writing, and linguistic aspects; such as grammar, vocabulary, language awareness, and language for cultural togetherness, and combining career and life skills (CLS) aspects consisting of leadership, initiative, flexibility, accountability, adaptation, social and cross-cultural skills, productivity and efficiency. Conclusion: (i) the content of Indonesian language teaching materials must adjust to the times, (ii) the teaching materials used today still have deficiencies in the aspects of content, and supporting completeness. Research suggestions: (i) teaching materials must be able to provide learning experiences and have an impact on graduates in their careers and lives, (ii) this research can be used as a reference in conducting development research.